The complex interplay of personal and external factors in medical students’ specialty decision-making: A qualitative study - Quang Thanh Nguyen; Minh Phan Ngoc Nguyen; Nhi Yen Bui; Minh Quang Ngo; Linh Vu Thuy Nguyen; Trang Thu Dang (PLoS ONE, 2025)
Background Medical students’ specialty decisions are shaped by a complex interaction of personal characteristics, academic experiences, social influences, and broader contextual factors. In lower-middle-income countries, where Western medical curricula are adapted to local educational and cultural contexts, little is known about how students make sense of these influences in shaping their future professional roles. This study aimed to explore how students interpret and construct their specialty choices in a newly established hybrid medical curriculum in Vietnam. Methods This qualitative study used an interpretive phenomenological approach. Semi-structured interviews were conducted with 27 medical students across all four academic years at a Vietnamese medical school. Participants were selected through purposive sampling to ensure diverse academic backgrounds and training levels. Interviews were thematically analyzed using an inductive framework to identify how students experienced and interpreted influences on their specialty decisions. Results Four interrelated themes emerged from the analysis. First, students described how personality traits shaped their emerging identity and influenced specialty preferences. Second, academic and extracurricular experiences, including clinical rotations, research, and volunteer work, were viewed as transformative encounters that clarified career direction. Third, students navigated financial hardship, family expectations, and academic pressure, often interpreting these constraints as factors in negotiating or compromising their career choices. Finally, the COVID-19 pandemic prompted moral reflection, with some students reaffirming frontline aspirations and others shifting toward specialties offering personal safety or opportunities for systemic impact. Conclusion Medical specialty choice is a reflective and identity-driven process shaped by personal dispositions, experiential learning, social pressures, and contextual disruptions. Rather than being solely determined by traits or external incentives, students engage in an evolving interpretation of who they are and what kind of doctor they wish to become. Medical education should incorporate reflective support systems to guide students through this complex process.